Trans faculty and queer battle fatigue: poetic (re)presentations of navigating identity politics in the academy. Issue 9 (21st October 2022) - Robinson, Sean
Abstract: Research on the experiences of trans* employees show that trans* individuals face disproportionate levels of harassment, discrimination, violence, and forms of aggression in the workplace. While broader organizational and workplace research exploring issues of trans* employees may be transferrable to higher education settings, higher education nevertheless has specific needs that make it distinctly different from non-higher education work environments. Although organizational scholars writing on workplace discrimination issues have offered recommendations for increasing trans-affirmation in workplace environments, little research has focused exclusively on trans* faculty on college and university campuses. Responding to calls for a nuanced understanding of trans* educators in more creative ways, this article (re)presents the experiences of six trans* identified post-secondary faculty in the format of a found poem that weaves together the voices of the participants into a collective narrative. When read through the lens of queer battle fatigue, the poem highlights the violence, marginalization, and forms of aggression experienced by trans* individuals that lead to feelings of exhaustion.